INCREASING EARLY DETECTION OF CHILDHOOD GROWTH DISORDERS WITH CHRONIC DISEASES IN COVID-19 ERA - Desy Wulandari; Wisnu Barlianto; Dyahris Koentartiwi; Hajeng Wulandari (Caring : Jurnal Pengabdian Masyarakat, 2022)
Impaired growth is still a problem that needs attention in Indonesia. There are still many incidents of children with short stature due to lack of nutrition, undernourished toddlers, and even malnutrition. Therefore, the detection of child growth still needs to be improved. The Covid-19 pandemic has made parents of patients afraid and anxious to take their children to health facilities, so that monitoring of their growth is neglected, especially in pediatric patients with chronic diseases. This community service activity is intended to provide training to parents of patients on how to measure anthropometric status in pediatric patients with chronic diseases so that parents are expected to be able to screen or detect growth disorders early and independently. Therefore, education and training are held with the aim of increasing the knowledge and skills of parents in examining the anthropometric status of children. Evaluation is done by asking questions and practicing anthropometric status checks at the beginning and end of the activity and good numbers of material uptake by participants are obtained so that participants can independently assess the child's anthropometric status and get an increase in skills. The knowledge of the patient's parents about awareness of growth and development screening is still lacking so that it can affect the detection of developmental disorders in children. With this activity, it can provide the ability of the patient's parents to equip themselves to monitor the growth of their child.